Understanding the Roles of Reflective Function and Emotion Control in Relationship Satisfaction - Kriplani, Sara (Université Saint-Paul / Saint Paul University, 2020)
Reflective function, defined as a person’s capacity to be curious about and open to their own and other peoples’ mind-states, is a concept that has gained attention in the attachment literature as a way to explain the affect-regulating function of attachment relationships (Fonagy, Gergely, Jurist, & Target, 2004). Attachment theorists have found that greater emotional control in couple relationships is linked to insecure attachment styles (Feeney, 1995) and that lower emotion control tends to lead to spouses feeling more satisfied within their marriage (Feeney, 1999). Reflective function is a factor which, to our knowledge, has never been investigated in terms of its effects on couple relationship functioning. Furthermore, the role of reflective function in emotion regulation in couple relationships has not yet been examined in the literature. As such, the aim of the current research was to investigate the role of reflective function and of emotion control in relation to relationship satisfaction within adult couples. We hypothesized that couples’ higher reflective function, and lower emotional control would be related to their higher relationship satisfaction and that couples’ higher reflective function would be related to their higher relationship satisfaction through their own lower emotional control. The participants in this study consisted of 27 couples involved in committed romantic relationships. Couples had to have been living together for at least one year and had to be over eighteen years of age. They were asked to complete a battery of questionnaires online. Results demonstrated that relationship satisfaction and reflective function were significantly related, but in the opposite direction than expected. We also found that emotion control and relationship satisfaction were significantly related, a finding that is consistent with previous research (e.g., Feeney, 1999).
Keywords: Reflective Function; Emotion Control; Relationship Satisfaction; Mentalization; Attachment